Using CleanWave Herbicide to Control Dogfennel in Pastures - Brent Sellers; Jason A. Ferrell (EDIS, 2007)
SS-AGR-283, a 2-page fact sheet by Brent Sellers and Jason Ferrell, describes how CleanWeave can be used to control dogfennel in Florida pastures. Published by the UF Department of Agronomy, October 2007.